Effectiveness of CBT in reducing anxiety to adolescents: A systematic literature review - Sarah Indah Jayanti; Yossie Susanti Eka Putri; Herni Susanti (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Anxiety disorders in adolescents are a growing global concern, with the World Health Organisation (WHO) reporting a prevalence of over 10% worldwide. In Indonesia, 15.6% of adolescents experience anxiety symptoms, which impact their social, academic, and emotional development. Cognitive Behavioural Therapy (CBT) has been proven effective in reducing anxiety, but evidence regarding its effectiveness in adolescents requires further synthesis. Purpose: To examine the effectiveness of CBT in reducing anxiety to adolescents. Methods: A systematic review was conducted of 10 studies (2013–2025) using databases such as ScienceDirect, Scopus, and Google Scholar. Inclusion criteria included randomised controlled trials (RCTs), quasi-experimental studies, and articles focusing on adolescents aged 10–19 years. The JBI was used as a critical appraisal tool to assess risk of bias, and data were synthesised thematically. Results: CBT significantly reduced anxiety symptoms in adolescents in various studies (p < 0.05). School-based CBT and internet-based CBT (iCBT) demonstrate equivalent effectiveness to traditional methods, with results persisting at follow-up (6–12 months). However, brief CBT interventions show limitations in terms of non-inferiority compared to standard protocols. Poorer outcomes are associated with inadequate adaptation of CBT techniques to developmental stages. Conclusion: CBT is an effective intervention for anxiety in adolescents, especially when integrated into school programmes or digital platforms. Adapting CBT to developmental stages and ensuring long-term monitoring are essential to maximise impact. Recommendations include expanding access to CBT in resource-limited settings and improving health policies to prioritise adolescent mental health.